Latin and music in the early modern era : education, theory, composition, performance and reception - Forgács, Robert (Lecturer) (Latinity and Classical reception in the early modern period., 2021)
Exploring the relationship between Latin and music during the early modern era, this volume focuses on the link between Latin and music in the educational system of the time, and the development and influence of musical humanism, especially in settings of classical and Neo-Latin texts.